Sociolinguistic Study on the Use of Regional Languages for Students of the Indonesian Language Study Program - Famel Zatrio; Kasmantoni Kasmantoni; Randi Randi (Journal of English Language and Education, 2026)
Regional languages play a significant role in preserving cultural identity and remain widely used in multilingual communities, including higher education settings. Although Indonesian functions as the official language in academic communication, regional languages continue to be actively employed by students in both academic and non-academic interactions. However, studies examining regional language use among university students from a sociolinguistic perspective remain limited. Therefore, this study aims to describe the forms of regional language use among students of the Indonesian Language Education Study Program at Fatmawati Sukarno State Islamic University of Bengkulu and identify the factors influencing their language choices. This study employed a descriptive qualitative approach within a sociolinguistic framework. Data were collected through observation, interviews, documentation, and recordings of students’ natural conversations and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that regional language use remains dominant, particularly in informal interactions, and is manifested through code-mixing, code-switching, language interference, and local dialect variation. These linguistic practices are influenced by ethnic background, social solidarity, environmental habits, cultural identity, and communicative comfort. The study highlights the importance of maintaining regional languages while strengthening positive attitudes toward the appropriate use of Indonesian in academic contexts.